Physiotherapie und physikalische Verfahren beim Fibromyalgiesyndrom: systematische Übersicht, Metaanalyse und Leitlinie - Winkelmann, Andreas; Schiltenwolf, Marcus (Der Schmerz, 2012)
BackgroundThe scheduled update to the German S3 guidelines on fibromyalgia syndrome (FMS) by the Association of the Scientific Medical Societies (“Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften”, AWMF; registration number 041/004) was planned starting in March 2011.Materials and methodsThe development of the guidelines was coordinated by the German Interdisciplinary Association for Pain Therapy (“Deutsche Interdisziplinären Vereinigung für Schmerztherapie”, DIVS), 9 scientific medical societies and 2 patient self-help organizations. Eight working groups with a total of 50 members were evenly balanced in terms of gender, medical field, potential conflicts of interest and hierarchical position in the medical and scientific fields.Literature searches were performed using the Medline, PsycInfo, Scopus and Cochrane Library databases (until December 2010). The grading of the strength of the evidence followed the scheme of the Oxford Centre for Evidence-Based Medicine. The formulation and grading of recommendations was accomplished using a multi-step, formal consensus process. The guidelines were reviewed by the boards of the participating scientific medical societies.Results and conclusionLow-to-moderate intensity aerobic exercise and strength training are strongly recommended. Chiropractic, laser therapy, magnetic field therapy, massage and transcranial current stimulation are not recommended.The English full-text version of this article is available at SpringerLink (under “Supplemental”).
First online: 05 July 2012
Gesehen am 25.06.2018